The Gut Microbiota and Associated Metabolites Are Altered in Sleep Disorder of Children With Autism Spectrum Disorders - Hua, Xueying; Zhu, Jiang; Yang, Ting; Guo, Min; Li, Qiu; Chen, Jie; Li, Tingyu (Frontiers in Psychiatry, 2020)
Background Autism spectrum disorder (ASD) is a type of neurodevelopmental disease that is frequently accompanied by sleep disorder. Herein, we investigated changes in the gut microbiota and its metabolites correlated with core symptoms and sleep problems in children with ASD. Methods One hundred and twenty children diagnosed with ASD based on Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria were enrolled in our study. The Autism Behavior Checklist (ABC), Social Responsiveness Scale (SRS), and Childhood Autism Rating Scale (CARS) were used to assess autism symptoms, and the Children Sleep Habits Questionnaire (CSHQ) was employed to evaluate sleep problems in children with ASD. The 120 children were divided into a sleep disorder group (n = 60) and a control group without sleep disorder (n = 60) according to the CSHQ answers. Illumina MiSeq analysis of 16S rRNA genes was used to compare differences in gut microbiota, and metabolomics analysis was employed to asses associated metabolites. Results SRS and CARS scores for the sleep disorder group were significantly higher than for the control group (p < 0.05). The abundances of butyrate-producing bacteria Faecalibacterium and Agathobacter were reduced significantly in the sleep disorder group (p < 0.05), and this was negatively correlated with CSHQ score (p = 0.007 and p = 0.014, respectively). The abundance of Agathobacter was also negatively associated with the ABC language score (p = 0.044). Furthermore, levels of 3-hydroxybutyric acid and melatonin were significantly lower (p < 0.05) while serotonin levels were higher (p < 0.05) in the sleep disorder group. The 3-hydroxybutyric acid level was positively associated with Faecalibacterium abundance (p = 0.000), and melatonin was positively associated with the abundance of Faecalibacterium (p = 0.036) and Agathobacter (p = 0.041). We also observed negative correlations between 3-hydroxybutyric acid and CSHQ (p = 0.000) and CARS (p = 0.009), between melatonin and CSHQ (p = 0.002) and ABC sensory score (p = 0.021), and a positive correlation between serotonin and CSHQ (p = 0.002) and ABC sensory score (p = 0.025). Conclusions ASD children with sleep disorder exhibited declines in the abundance of Faecalibacterium and Agathobacter, decreased levels of 3-hydroxybutyric acid and melatonin, and an increase in serotonin. These changes may aggravate sleep problems and core symptoms in children with ASD.